From Words to Understanding: Analyzing Lexical Density and Readability in Student Writing - Br Sembiring, Franinta Egia D. R (LingPoet: Journal of Linguistics and Literary Research, 2025)
This study examines high school students' English writing skills after a month in an English course. The research used a qualitative methodology to analyse 10 student writings, assessing lexical density and readability levels, and their impact on comprehension and writing quality. Lexical density, the proportion of content words to function words, indicates informational richness, whereas readability evaluates the comprehensibility of text, measured by measures such as ASL and ASW. Results show that lexical density in student writings ranges between 48.54% and 56.07%, indicating moderately complex texts that may challenge learners depending on their proficiency. Texts with higher lexical density, characterized by frequent use of nouns and adjectives, present richer information, making them suitable for advanced learners but potentially difficult for beginners. Readability scores reveal that most texts are classified as "Very Easy" to "Easy," suggesting accessibility for lower-intermediate students. Only one text falls into the "Fairly Easy" category, indicating a progression toward more complex material. These findings show the need for teaching materials that match students' language skills, offering challenges to improve learning while staying understandable. The study suggests using glossaries or guiding questions for complex texts to help students of all levels understand better and learn more effectively.